Comparative tests of single single and three phase motors - Peckham, John J.; Weaver, Chauncey Iles (My University, 1906)
Introduction: 2 HP Three Phase Induction Motor, No. 83362, Type 1, Form K. 1800 R.P.M., 110 Volts, 60 Cycles, 12 amperes. The primary or rotor of the motor is mounted in a hollow cylindrical frame of cast iron. This frame also forms the base of the machine and supports two end plates which contain the rotor bearings. The bearings consist of brass boxes arranged to be lubricated by two rings in each bearing. These rings revolve as the shaft turns carrying the oil from a chamber below the bearings. The primary consists of an iron core which is built up of sheet steel stampings. The core is firmly bolted to the frame. The conductors, which are copper wires or bars, depending upon the size of the machine, are placed in grooves in the core. These coils are insulated from the core and from each other where more than one conductor is placed in a slot. The windings, which are (y) connected, are held in the slots by thin wedges of tough wood, to protect the winding from mechanical injury, and also from the mechanical pull due to the reaction of the flux in the rotor. The secondary member or rotor is built up of laminated sheet steel. The laminae are insulated from each other by sheets of tissue paper or by a coating of japan, in order to reduce the loss by eddy currents which are induced by the flux. The conductors in this member are heavy copper bars which are short circuited at the ends of the rotor by heavy copper plates.
Citation: Peckham, John J. and Weaver, Chauncey Iles. Comparative tests of single single and three phase motors. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Single Phase Motor; Three Phase Motor; Motors; Theses